Seasonal Changes in Copper and Cobalt Concentrations of Pinus nigra L., Cedrus libani and Cupressus arizonica Leaves to Monitor the Effects of Pollution in Elazig (Turkey) - Karaaslan, Nagihan M.; Yaman, Mehmet (Office Spectroscopy & Spectral Analysis, 2013)
The aim of this study is to examine seasonal changes in Cu and Co concentrations of three plant species for monitoring the effects of pollution in Elazig, Turkey. For this purpose, the leaves of the Pinus nigra L., Cedrus libani and Cupressus arizonica together with soil samples were collected from different points depending on traffic intensity, nearness the city center and cement factory as well as control location during different months of the year. Flame atomic absorption spectrophotometer (FAAS) was used for measurement of the metals in clear digests after the dry ashing method. Copper and Co concentrations were in the ranges from 1.3 to 2.6 mg . kg(-1) and
Keywords: Copper; cobalt; biomonitor; Pinus nigra L.; Cedrus libani; Cupressus arizonica